2022
DOI: 10.1186/s41938-022-00607-6
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal potential of indigenous isolates of Entomopathogenic Nematodes (EPNs) against tobacco cutworm, Spodoptera litura Fabricius (Lepidoptera: Noctuidae)

Abstract: Background Entomopathogenic nematodes (EPNs) have been regarded as the most convenient strategy for insect pest management. The native strains of EPNs: Heterorhabditis bacteriophora EUPT-SD, H. bacteriophora EUPT-R, H. bacteriophora EUPT-KN, H. bacteriophora EUPT-K and H. bacteriophora EUPT-H isolated from mid-Himalayan region of Himachal Pradesh were tested in laboratory for their multiplication and virulence against 3rd and 4th larval instars of the tobacco cutworm, Spodoptera litura Fabriciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Amongst both of these treatments, applications of different concentrations of X. nematophila caused rapid infectivity followed by insect mortality. The observations of the current findings are supported by previous observations that showed 100% larval mortality in the early instars after 96 h [45,[52][53][54]. It was also suggested that increased exposure time significantly increased larval mortality and vice versa [55].…”
Section: Discussionsupporting
confidence: 90%
“…Amongst both of these treatments, applications of different concentrations of X. nematophila caused rapid infectivity followed by insect mortality. The observations of the current findings are supported by previous observations that showed 100% larval mortality in the early instars after 96 h [45,[52][53][54]. It was also suggested that increased exposure time significantly increased larval mortality and vice versa [55].…”
Section: Discussionsupporting
confidence: 90%
“…The adult and larval stages of the test insect were collected from the agricultural field and brought to the laboratory. The rearing was done in the laboratory using the methodology followed by the methods of Tomar and Thakur [32].…”
Section: Rearing Of Test Insects In the Laboratorymentioning
confidence: 99%
“… 28 , 29 Biological control presents a sustainable solution to tackle this notorious pest problem. Various biological control agents, such as predators, 30 parasitoids, 31 entomopathogenic nematodes, 32 bacteria, 33 fungi 34 36 and nucleopolyhydrousvirus (NPVs), 37 are widely employed and its impact on physiological and biochemical activities.…”
Section: Introductionmentioning
confidence: 99%